Pengaruh Persepsi Pasien tentang Pengembangan Diri, Etika, dan Penampilan Fisik Tenaga Kesehatan terhadap Minat Kunjung Ulang yang di Mediasi Brand Image Klinik Penelitian Kuantitatif di Klinik Mitra Tamzil Kabupaten Sukabumi - Larasati Larasati; Endang Komara; Achmad Dheni Suwardhani (VISA: Journal of Vision and Ideas, 2026)
This study aims to analyze the influence of self-development, ethics, and physical appearance of health workers on patient's intention to return to the Mitra Tamzil Clinic, with brand image as a mediating variable. The study used a quantitative method with a cross-sectional analytical observational design, involving 63 outpatients selected by random sampling. Data were collected through questionnaires, observations, documentation, and in-depth interviews, then analyzed using regression tests to examine the direct and indirect effects between variables. The results showed that self-development of health workers significantly influenced patient's intention to return both directly and through brand image. The indirect effect through brand image was greater than the direct effect (0.030 < 0.066), while the regression coefficient of self-development was 0.272 with a t-count of 2.245 > t-table of 2.030, and a contribution of 68.89%. Healthcare worker ethics also significantly influenced repeat visit intention, with the indirect effect through brand image being greater than the direct effect (0.101 < 0.224), with a regression coefficient of 0.139, a calculated t-value of 2.258, and a contribution of 29.05%. Healthcare workers' physical appearance significantly influenced both directly and indirectly through brand image (0.124 < 0.278), with a regression coefficient of 0.106, a calculated t-value of 2.740, and a contribution of 63.20%. Brand image directly significantly influenced repeat visit intention, with a regression coefficient of 0.272, a calculated t-value of 2.660, and a contribution of 61.93%. Overall, this study confirms that healthcare workers' self-development, ethics, and physical appearance significantly increase patient repeat visit intention, both through direct effects and through brand image as a mediating variable. These findings demonstrate the importance of improving human resource quality and clinic image in building patient loyalty and maintaining expectations of quality healthcare services.